2007
DOI: 10.1063/1.2797378
|View full text |Cite
|
Sign up to set email alerts
|

Chaos suppression through asymmetric coupling

Abstract: We study pairs of identical coupled chaotic oscillators. In particular, we have used Roessler ͑in the funnel and no funnel regimes͒, Lorenz, and four-dimensional chaotic Lotka-Volterra models. In all four of these cases, a pair of identical oscillators is asymmetrically coupled. The main result of the numerical simulations is that in all cases, specific values of coupling strength and asymmetry exist that render the two oscillators periodic and synchronized. The values of the coupling strength for which this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Synchronization regime has been analyzed using different coupling schemes (symmetric or asymmetric) and considering the coupling as a direct function of the error between both systems (acting as a feedback loop). Phase synchronization (PS) has been obtained using selected values for parameters that must be fine-tuned to fit the Lyapunov exponent windows [21]. The synchronized regimes obtained in this case are not very stable and depend strongly on the coupling coefficient value.…”
Section: The Coupled Systemmentioning
confidence: 99%
“…Synchronization regime has been analyzed using different coupling schemes (symmetric or asymmetric) and considering the coupling as a direct function of the error between both systems (acting as a feedback loop). Phase synchronization (PS) has been obtained using selected values for parameters that must be fine-tuned to fit the Lyapunov exponent windows [21]. The synchronized regimes obtained in this case are not very stable and depend strongly on the coupling coefficient value.…”
Section: The Coupled Systemmentioning
confidence: 99%
“…Bragard et al [20] observed chaos suppression in chaotic oscillators with bidirectional asymmetric coupling. They found that adequate asymmetry and coupling between two identical chaotic oscillators may force their dynamics towards regular periodic oscillations.…”
mentioning
confidence: 99%
“…Phase synchronization (PS) has been obtained using selected values for parameters that must be fine-tuned to fit Lyapunov exponent windows. 25 The synchronized regimes obtained in this case are not too stable and depend strongly on the coupling coefficient.…”
Section: Coupling Effectsmentioning
confidence: 77%
“…Synchronization induced by asymmetric coupling (masterslave configuration) of two or more autonomous oscillators is a well-known effect. 25,28 In four dimensional systems (4D) with symmetrical coupling of two identical T-B systems, one variable (x) has been presented in Ref. 28.…”
Section: Coupling Effectsmentioning
confidence: 99%
See 1 more Smart Citation